Dynamic and static volatility interruptions: Evidence from the Korean stock markets - Kyong Shik Eom; Kyungyoon Kwon; Sung Chae La; Jong-Ho Park (Journal of Risk and Financial Management, 2022)
We conducted a comprehensive analysis on the sequential introductions of dynamic and static volatility interruptions (VIs) in the Korean stock markets. The Korea Exchange introduced VIs to improve price formation, and to limit risk to investors from brief periods of abnormal volatility for individual stocks. We found that dynamic VI is effective in price stabilization and discovery, while the effect of static VI is limited. The static VI functions similarly to the pre-existing price-limit system; this accounts for its limited incremental benefit.
Keywords: G10; G18; G20; 330; volatility safeguards; volatility interruption; call auction; price stabilization; price discovery